A BOPHY based fluorescent probe for Hg2+via NTe2 chelation. Issue 26 (21st June 2022) - Malankar, Gauri S.; Shelar, Divyesh S.; M., Manikandan; Patra, Malay; Butcher, Ray J.; Manjare, Sudesh T.
Abstract : The first tellurium derivative of BOPHY is reported. The probe could detect Hg 2+ inside HeLa cells with an instantaneous fluorescence turn-on response in the nanomolar range. Abstract : A BOPHY-based organotellurium-containing probe was synthesized and characterized via single crystal XRD for the selective and sensitive detection of Hg 2+ over other metal ions. The probe detects Hg 2+ in less than 1 s with a 2.5-fold enhancement in fluorescent intensity. Due to the chalcogenophilicity of mercury, Hg 2+ was facilely trapped in the NTe2 chelating cavity of the probe. The probe can detect Hg 2+ in the nanomolar range (62 nM) and it showed reversibility with S 2− ions. The sensitivity of the probe for the detection of Hg 2+ was confirmed in living HeLa cells.